The Effect of Utilizing The Shopee E-Commerce Platform on Fashion Buying Interest: Case Study Shopee Video Deefcraft SME - Anna Fitriana; Dicki Kusmayadi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This research aims to determine the extent to which the influence of Shopee Video @deefcraftcenter content on the buying interest of followers on the Shopee Deefcraft Center account. to answer these problems, researchers analyze photo content, video content, and captions on exploratory interest, transactional interest, referential interest and preferential interest. This study utilizes a quantitative methodology involving surveys and regression analysis tools. The study's population comprises 3,800 individuals, from which a sample of 100 participants was extracted. The results demonstrate that photographic content considerably affects buy intentions, although video content and captions also play a substantial role in purchasing decisions. Shopee video content significantly influences exploratory, transactional, referential, and preferential interest. This study concludes that a modest, substantial, and unidirectional relationship exists between the influence of Shopee videos and buy intention, suggesting that purchasing interest is also influenced by additional criteria such as service quality, product quality, and cost. The data processing and hypothesis testing outcomes indicate the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha). Suggestions for the Shopee Video @deefcraftcenter account are expected to pay attention to Shopee Video content by maintaining content quality, creating content that interacts more with followers and consistency in uploading content by utilizing the features available at Shopee Video in order to attract more consumer buying interest. This research unveils significant implications for brands and marketers using platforms like Shopee to engage potential buyers. By highlighting that Shopee video content, alongside images and captions, plays a pivotal role in shaping various aspects of consumer interest, the findings encourage brands to refine their content strategies. The data suggests that not only must the quality of visual and textual elements be prioritized, but also that fostering a deeper connection with followers through interactive and consistent uploads can enhance buyer engagement. Companies can leverage these insights to tailor their marketing efforts more effectively, thereby increasing purchase intentions among consumers. In essence, this study underscores the importance of integrating quality content with consistent interaction to nurture and boost consumer interest, ultimately driving sales and fostering brand loyalty.